Review of the prevalence of Mild Behavioral Impairment subdomains in populations from cognitively normal to Mild Cognitive Impairment according to International Society for Advanced Alzheimer's Research and Treatment criteria - Virginia Quicchi (Perspectivas Metodológicas​)
A systematic review analyzes the frequency of Mild Behavioral Impairment (MBI) subdomains according to the International Society to Advance Alzheimer’s Research and Treatment (ISTAART) criteria in populations ranging from cognitively normal to Mild Cognitive Impairment (MCI) to determine the most frequent symptomatic manifestations. Using the PRISMA methodology, 13 articles were selected from the PubMed and ProQuest databases, with a total of 21.457 older adults. The most frequent MBI domains were loss of impulse control, affective dysregulation, decreased motivation and the less frequent social inadequacy and alteration of thought content.